Low-Dose-Whole-Lung Radiotherapy for Older Patients with Coronavirus Disease (Covid-19) Pneumonia: A Phase I-II Prospective Non-Randomized Protocol by the International Geriatric Radiotherapy Group - Nguyen, Nam P; Arenas, Meritxell; Vuong, Te; Zamagni, Alice; Vinh-Hung, Vincent; Berardino, De Bari; Galalae, Razvan; Farid, Ahmed; Motta, Micaela; Lara, Pedro Carlos; Bonet, Marta; Karlsson, Ulf; et al. (Archives of Clinical and Biomedical Research, 2021)
Background: Coronavirus disease 19 (COVID-19) carries a high mortality rate among older patients and minorities such as ethnic Africans and Latinos. These patients suffer from chronic inflammation that may turn into a cytokine storm when infection occurs, in addition to frequently possessing multiple comorbidity factors that may also account for their higher mortality. Even though multiple organ failure results from the cytokine storm, it is pneumonia and respiratory failure that often lead to death. Low-dose-whole-lung radiotherapy (LDWLRT) may modulate the inflammatory response and decrease the need for artificial ventilation, thus improving the mortality rate. Methods: A phase I-II prospective trial, enrolling 500 patients, aged 65 years old or above from 25 countries, will be conducted to investigate the impact of LDWLRT on the mortality rate in COVID-19 patients. Selected patients will have developed viral pneumonia that does not require artificial ventilation. These patients will be followed for a year after receiving radiotherapy. The impact of the residual inflammation will be assessed using the ordinal scale. Mortality rates will also be compared among different ethnic groups and correlated with their cytokine response to the virus and number of co-morbidities. Results: Patients have been recruited in an institution in Mexico as per protocol. Patient recruitment is scheduled at another institution in Canada pending Institutional Review Board approval. The preliminary results will be used to apply for funding. Discussion and importance of the study: We postulate that LDWLRT may improve survival rates in all patients by preventing the need for artificial ventilation, which is associated with a high mortality. The differences in inflammatory response among ethnic groups prior to and following radiotherapy will serve as a valuable baseline f